Characteristics of the Teachers of Gifted Students in Schools for Gifted and Talented Students in the Hashemite Kingdom of Jordan - Samer Mutlq Mohammad Ayasrah (Universiti Sains Islam Malaysia, 2024)
This study mainly aimed to identify the main dimensions and characteristics concerning the teachers of the gifted and talented students from the viewpoint of both gifted and talented students and their teachers, to highlight differences in estimating these properties from their point of view, to determine the impact of these characteristics on academic achievement of the gifted and talented students. The study was conducted on (691) students and (207) teachers in King Abdullah II Schools for excellence and the Jubilee School in the Hashemite Kingdom of Jordan. The study was able to identify the main dimensions of the characteristics of the teachers who taught talented and gifted students. The results of factor analysis for the students revealed that seven factors accumulated around the study variables, the cumulative interpreted value of these factors is (53,107 %) and regarding the teachers the study revealed nine factors accumulated around the study variables, the cumulative interpreted value of these factors is (64.661%). The T-test results show that there are significant differences between the students and teachers regarding their perspective toward the characteristics of the teachers of the gifted and talented students in favour of teachers in all dimensions.The findings also revealed that there are no significant differences in estimating the features due to gender variable in any dimensions of the features. Multiple regression analysis results showed that (0.502%) of the shift in student's academic achievement could be explained by the variables (personal, personal emotional, cognitive, educational personal, educational, emotional personal educational, emotional) and the rest percentage assigned to other variables. In addition, multiple regression analysis results revealed that 11 characteristics have a strong impact and ability to interpret the shift in student academic achievement. The study concluded recommendations concerning reviewing preparation programs of rehabilitating and training teachers of gifted and talented students which are presented to them before and during the service by combining n them the set of properties revealed from the results of the study, which will contribute to meet the needs of gifted and talented students and their teachers.